Sensitivity of cholecystokinin receptors to membrane cholesterol content - Desai, Aditya J.; Miller, Laurence J. (Frontiers in Endocrinology, 2012)
Cholesterol represents a structurally and functionally important component of the eukaryotic cell membrane, where it increases lipid order, affects permeability, and influences the lateral mobility and conformation of membrane proteins. Several G protein-coupled receptors have been shown to be affected by the cholesterol content of the membrane, with functional impact on their ligand binding and signal transduction characteristics. The effects of cholesterol can be mediated directly by specific molecular interactions with the receptor and/or indirectly by altering the physical properties of the membrane. This review focuses on the importance and differential effects of membrane cholesterol on the activity of cholecystokinin (CCK) receptors. The type 1 CCK receptor is quite sensitive to its cholesterol environment, while the type 2 CCK receptor is not. The possible structural basis for this differential impact is explored and the implications of pathological states, such as metabolic syndrome, in which membrane cholesterol is increased and CCK1R function may be abnormal are discussed. This is believed to have substantial potential importance for the development of drugs targeting the CCK receptor.